(untitled) (Critical Journal of Social Sciences, 2026)
The National Education Policy (NEP) 2020 is a revolutionary turning point to the educational practices in the country, with a special focus on higher education and use of the Indian Knowledge System (IKS). IKS is built on the existing cultural, philosophical and intellectual heritage of India and is all encompassing in nature targeting education, empowerment, development, leadership, and public service with infusing critical thinking, ethics and sustainable development. The purpose of the policy is to bridge the gap between the ancient teachings and modern requirements and develop an education system that is globally competitive and yet ethnocentric taking the best of teachings from the two systems. . The National Education Policy 2020 within higher education institutions envisions integrating IKS, promoting research, cultural exchanges, and restructuring of teaching where traditional knowledge goes hand in hand with scientific knowledge as it exists. The attempt has been made in this article to describe the contribution of NEP 2020 to the improvement of higher education in India through incorporation of the Indian Knowledge System with a particular focus on the aspects of pedagogy, research and positioning of India in the knowledge economy. Such a policy which seeks to incorporate Indian knowledge systems IKS can bring about a cultural and educational renaissance and produce holistic graduates capable of dealing with the complexities of the 21st century while preserving the cultural ethos of India.